2013
DOI: 10.1098/rsif.2012.0765
|View full text |Cite
|
Sign up to set email alerts
|

Osteoconductive phosphoserine-modified poly(ε-lysine) dendrons: synthesis, titanium oxide surface functionalization and response of osteoblast-like cell lines

Abstract: The lack of direct bonding between the surface of an implant and the mineralized bony tissue is among the main causes of aseptic loosening in titaniumbased implants. Surface etching and ceramic coatings have led to improved osteointegration, but their clinical performance is still limited either by partial bonding or by coating delamination. In this work, a solid-phase synthesis method has been optimized to produce poly(1-lysine) dendrons, the outermost branching generation of which is functionalized by phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Chemical and structural analysis, with X-ray diffraction and electron microscopy, revealed that phosphorylated amino acids (i.e., phosphoserine) accelerated the setting, improved the mechanical strength, and enhanced the handling properties by (a) forming a macroscale organic phase that covers the surface of αTCP particles, thereby preventing the dissolution or reorganization of αTCP, and (b) facilitating the nucleation of nanoscale, amorphous calcium phosphate to produce a nanoscale organic/inorganic composite material. Phosphoserine was selected for this study because it is predominantly found in phosphoproteins that are involved in a wide range of biological processes; from adhesion, in marine “bioglues” [20,21,22], tissue adhesion, cohesion, and load dissipation in animals, to biomineralization, via matrix proteins [1,3,23], and matrix vesicles [2]. We hypothesized that some of these interesting biological and chemical properties might be recreated, to a limited extent, by incorporating phosphoserine into CPCs [8].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical and structural analysis, with X-ray diffraction and electron microscopy, revealed that phosphorylated amino acids (i.e., phosphoserine) accelerated the setting, improved the mechanical strength, and enhanced the handling properties by (a) forming a macroscale organic phase that covers the surface of αTCP particles, thereby preventing the dissolution or reorganization of αTCP, and (b) facilitating the nucleation of nanoscale, amorphous calcium phosphate to produce a nanoscale organic/inorganic composite material. Phosphoserine was selected for this study because it is predominantly found in phosphoproteins that are involved in a wide range of biological processes; from adhesion, in marine “bioglues” [20,21,22], tissue adhesion, cohesion, and load dissipation in animals, to biomineralization, via matrix proteins [1,3,23], and matrix vesicles [2]. We hypothesized that some of these interesting biological and chemical properties might be recreated, to a limited extent, by incorporating phosphoserine into CPCs [8].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphoserine modified cements (PMCs), including the non-adhesive cement formulations studied by Reinstorf et al [29,30,31], have been investigated for hard tissue applications because: (a) many of the chemical and physical properties of cured/set PMC mirror those of the mineral phase of bone (i.e., strong compressive strength [31], presence of amorphous and crystalline calcium phosphate, etc. ); (b) phosphoserine exerts a direct stimulatory effect on the proliferation and differentiation of osseous cell types, including osteoblasts [32,33,34,35,36], stem cells [36,37], and endothelial cells [32,33,34,35,36], and can increase the expression of bone morphogenetic protein (BMP-2) and runt-related transcription factor (RUNX2) [32,36]; and (c) can improve the physical properties, (i.e., high compressive strength [31], strong bonding to calcified tissue surfaces [38,39,40], etc. ), and immune-/histo-compatibility, of cements in vivo (i.e., by accelerating resorption and replacement of cement with new bone, and increasing the numbers of recruited macrophages and osteoclasts) [35,41].…”
Section: Introductionmentioning
confidence: 99%
“…96 It has been revealed in many research studies that a dendritic polymer coated on the titanium surface can promote HAP formation and improve biocompatibility of titanium. 97,98 It is noteworthy that this dendritic polymer-titanium hybrid material can adhere osteoblast cells and stimulate their proliferation or differentiation in short time. This material opens up a new developing path for osteointegrative metal implants.…”
Section: Bioinspired Artificial Proteins and Peptidesmentioning
confidence: 99%